\documentclass{article} \input{../../preamble} \externaldocument[C:1:07:]{Chapter_1_07}[Chapter_1_07.pdf] \newcommand{\lean}[1]{\leanref {./Chapter\_1\_11.html\#Apostol.Chapter\_1\_11.#1} {Apostol.Chapter\_1\_11.#1}} \begin{document} \header{Exercises 1.11}{Tom M. Apostol} \section*{Exercise 4}% \label{sec:exercise-4} Prove that the greatest-integer function has the properties indicated: \subsection*{\verified{Exercise 4a}}% \label{sub:exercise-4a} $\floor{x + n} = \floor{x} + n$ for every integer $n$. \begin{proof} \lean{exercise\_4a} \divider Let $x$ be a real number and $n$ an integer. Let $m = \floor{x + n}$. By definition of the floor function, $m$ is the unique integer such that $m \leq x + n < m + 1$. Then $m - n \leq x < (m - n) + 1$. That is, $m - n = \floor{x}$. Rearranging terms we see that $m = \floor{x} + n$ as expected. \end{proof} \subsection*{\verified{Exercise 4b}}% \label{sub:exercise-4b} $\floor{-x} = \begin{cases} -\floor{x} & \text{if } x \text{ is an integer}, \\ -\floor{x} - 1 & \text{otherwise}. \end{cases}$ \begin{proof} \ \vspace{6pt} \lean{exercise\_4b\_1} \lean{exercise\_4b\_2} \divider There are two cases to consider: \paragraph{Case 1}% Suppose $x$ is an integer. Then $x = \floor{x}$ and $-x = \floor{-x}$. It immediately follows that $$\floor{-x} = -x = -\floor{x}.$$ \paragraph{Case 2}% Suppose $x$ is not an integer. Let $m = \floor{-x}$. By definition of the floor function, $m$ is the unique integer such that $m \leq -x < m + 1$. Equivalently, $-m - 1 < x \leq -m$. Since $x$ is not an integer, it follows $-m - 1 \leq x < -m$. Then, by definition of the floor function, $\floor{x} = -m - 1$. Solving for $m$ yields $$\floor{-x} = m = -\floor{x} - 1.$$ \paragraph{Conclusion}% The above two cases are exhaustive. Thus $$\floor{-x} = \begin{cases} -\floor{x} & \text{if } x \text{ is an integer}, \\ -\floor{x} - 1 & \text{otherwise}. \end{cases}$$ \end{proof} \subsection*{\verified{Exercise 4c}}% \label{sub:exercise-4c} $\floor{x + y} = \floor{x} + \floor{y}$ or $\floor{x} + \floor{y} + 1$. \begin{proof} \lean{exercise\_4c} \divider Rewrite $x$ and $y$ as the sum of their floor and fractional components: $x = \floor{x} + \{x\}$ and $y = \floor{y} + \{y\}$. Now \begin{align} \floor{x + y} & = \floor{\floor{x} + \{x\} + \floor{y} + \{y\}} \nonumber \\ & = \floor{\floor{x} + \floor{y} + \{x\} + \{y\}} \nonumber \\ & = \floor{x} + \floor{y} + \floor{\{x\} + \{y\}} & \text{\nameref{sub:exercise-4a}} \label{sub:exercise-4c-eq1} \end{align} There are two cases to consider: \paragraph{Case 1}% Suppose $\{x\} + \{y\} < 1$. Then $\floor{\{x\} + \{y\}} = 0$. Substituting this value into \eqref{sub:exercise-4c-eq1} yields $$\floor{x + y} = \floor{x} + \floor{y}.$$ \paragraph{Case 2}% Suppose $\{x\} + \{y\} \geq 1$. Because $\{x\}$ and $\{y\}$ are both less than $1$, $\{x\} + \{y\} < 2$. Thus $\floor{\{x\} + \{y\}} = 1$. Substituting this value into \eqref{sub:exercise-4c-eq1} yields $$\floor{x + y} = \floor{x} + \floor{y} + 1.$$ \paragraph{Conclusion}% Since the above two cases are exhaustive, it follows $\floor{x + y} = \floor{x} + \floor{y}$ or $\floor{x} + \floor{y} + 1$. \end{proof} \subsection*{\proceeding{Exercise 4d}}% \label{sub:exercise-4d} $\floor{2x} = \floor{x} + \floor{x + \frac{1}{2}}.$ \begin{proof} \lean{exercise\_4d} \divider This is immediately proven by applying Hermite's Identity as shown in \nameref{sec:exercise-5}. \end{proof} \subsection*{\proceeding{Exercise 4e}}% \label{sub:exercise-4e} $\floor{3x} = \floor{x} + \floor{x + \frac{1}{3}} + \floor{x + \frac{2}{3}}.$ \begin{proof} \lean{exercise\_4e} \divider This is immediately proven by applying Hermite's Identity as shown in \nameref{sec:exercise-5}. \end{proof} \section*{\proceeding{Exercise 5}}% \label{sec:exercise-5} The formulas in Exercises 4(d) and 4(e) suggest a generalization for $\floor{nx}$. State and prove such a generalization. \note{The stated generalization is known as "Hermite's Identity."} \begin{proof} \lean{exercise\_5} \divider We prove that for all natural numbers $n$ and real numbers $x$, the following identity holds: \begin{equation} \label{sec:exercise-5-eq1} \floor{nx} = \sum_{i=0}^{n-1} \floor{x + \frac{i}{n}} \end{equation} By definition of the floor function, $x = \floor{x} + r$ for some $r \in \ico{0}{1}$. Define $S$ as the partition of non-overlapping subintervals $$\ico{0}{\frac{1}{n}}, \ico{\frac{1}{n}}{\frac{2}{n}}, \ldots, \ico{\frac{n-1}{n}}{1}.$$ By construction, $\cup\; S = \ico{0}{1}$. Therefore there exists some $j \in \mathbb{N}$ such that \begin{equation} \label{sec:exercise-5-eq2} r \in \ico{\frac{j}{n}}{\frac{j+1}{n}}. \end{equation} With these definitions established, we now show the left- and right-hand sides of \eqref{sec:exercise-5-eq1} evaluate to the same number. \paragraph{Left-Hand Side}% Consider the left-hand side of identity \eqref{sec:exercise-5-eq1}. By \eqref{sec:exercise-5-eq2}, $nr \in \ico{j}{j + 1}$. Therefore $\floor{nr} = j$. Thus \begin{align} \floor{nx} & = \floor{n(\floor{x} + r)} \nonumber \\ & = \floor{n\floor{x} + nr} \nonumber \\ & = \floor{n\floor{x}} + \floor{nr}. \nonumber & \text{\nameref{sub:exercise-4a}} \\ & = \floor{n\floor{x}} + j \nonumber \\ & = n\floor{x} + j. \label{sec:exercise-5-eq3} \end{align} \paragraph{Right-Hand Side}% Now consider the right-hand side of identity \eqref{sec:exercise-5-eq1}. We note each summand, by construction, is the floor of $x$ added to a nonnegative number less than one. Therefore each summand contributes either $\floor{x}$ or $\floor{x} + 1$ to the total. Letting $z$ denote the number of summands that contribute $\floor{x} + 1$, we have \begin{equation} \label{sec:exercise-5-eq4} \sum_{i=0}^{n-1} \floor{x + \frac{i}{n}} = n\floor{x} + z. \end{equation} The value of $z$ corresponds to the number of indices $i$ that satisfy $$\frac{i}{n} \geq 1 - r.$$ By \eqref{sec:exercise-5-eq2}, it follows \begin{align*} 1 - r & \in \ioc{1 - \frac{j+1}{n}}{1-\frac{j}{n}} \\ & = \ioc{\frac{n - j - 1}{n}}{\frac{n - j}{n}}. \end{align*} Thus we can determine the value of $z$ by instead counting the number of indices $i$ that satisfy $$\frac{i}{n} \geq \frac{n - j}{n}.$$ Rearranging terms, we see that $i \geq n - j$ holds for $z = (n - 1) - (n - j) + 1 = j$ of the $n$ summands. Substituting the value of $z$ into \eqref{sec:exercise-5-eq4} yields \begin{equation} \label{sec:exercise-5-eq5} \sum_{i=0}^{n-1} \floor{x + \frac{i}{n}} = n\floor{x} + j. \end{equation} \paragraph{Conclusion}% Since \eqref{sec:exercise-5-eq3} and \eqref{sec:exercise-5-eq5} agree with one another, it follows identity \eqref{sec:exercise-5-eq1} holds. \end{proof} \section*{\unverified{Exercise 6}}% \label{sec:exercise-6} Recall that a lattice point $(x, y)$ in the plane is one whose coordinates are integers. Let $f$ be a nonnegative function whose domain is the interval $[a, b]$, where $a$ and $b$ are integers, $a < b$. Let $S$ denote the set of points $(x, y)$ satisfying $a \leq x \leq b$, $0 < y \leq f(x)$. Prove that the number of lattice points in $S$ is equal to the sum $$\sum_{n=a}^b \floor{f(n)}.$$ \begin{proof} Let $i = a, \ldots, b$ and define $S_i = \mathbb{N} \cap \ioc{0}{f(i)}$. By construction, the number of lattice points in $S$ is \begin{equation} \label{sec:exercise-6-eq1} \sum_{n = a}^b \abs{S_n}. \end{equation} All that remains is to show $\abs{S_i} = \floor{f(i)}$. There are two cases to consider: \paragraph{Case 1}% Suppose $f(i)$ is an integer. Then the number of integers in $\ioc{0}{f(i)}$ is $f(i) = \floor{f(i)}$. \paragraph{Case 2}% Suppose $f(i)$ is not an integer. Then the number of integers in $\ioc{0}{f(i)}$ is the same as that of $\ioc{0}{\floor{f(i)}}$. Once again, that number is $\floor{f(i)}$. \paragraph{Conclusion}% By cases 1 and 2, $\abs{S_i} = \floor{f(i)}$. Substituting this identity into \eqref{sec:exercise-6-eq1} finishes the proof. \end{proof} \section*{Exercise 7}% \label{sec:exercise-7} If $a$ and $b$ are positive integers with no common factor, we have the formula $$\sum_{n=1}^{b-1} \floor{\frac{na}{b}} = \frac{(a - 1)(b - 1)}{2}.$$ When $b = 1$, the sum on the left is understood to be $0$. \note{When $b = 1$, the proofs of (a) and (b) are trivial. We continue under the assumption $b > 1$.} \subsection*{\unverified{Exercise 7a}}% \label{sub:exercise-7a} Derive this result by a geometric argument, counting lattice points in a right triangle. \begin{proof} Let $f \colon [1, b - 1] \rightarrow \mathbb{R}$ be given by $f(x) = ax / b$. Let $S$ denote the set of points $(x, y)$ satisfying $1 \leq x \leq b - 1$, $0 < y \leq f(x)$. By \nameref{sec:exercise-6}, the number of lattice points of $S$ is equal to the sum \begin{equation} \label{sub:exercise-7a-eq1} \sum_{n=1}^{b-1} \floor{f(n)} = \sum_{n=1}^{b-1} \floor{\frac{na}{b}}. \end{equation} Define $T$ to be the triangle of width $w = b$ and height $h = f(b) = a$ as $$T = \{ (x, y) : 0 < x < b, 0 < y \leq f(x) \}.$$ By construction, $T$ does not introduce any additional lattice points. Thus $S$ and $T$ have the same number of lattice points. Let $H_L$ denote the number of boundary points on $T$'s hypotenuse. We prove that (i) $H_L = 2$ and (ii) that $T$ has $\frac{(a - 1)(b - 1)}{2}$ lattice points. \paragraph{(i)}% \label{par:exercise-7a-i} Consider the line $L$ overlapping the hypotenuse of $T$. By construction, $T$'s hypotenuse has endpoints $(0, 0)$ and $(b, a)$. By hypothesis, $a$ and $b$ are positive, excluding the possibility of $L$ being vertical. Define the slope of $L$ as $$m = \frac{a}{b}.$$ $H_L$ coincides with the number of indices $i = 0, \ldots, b$ such that $(i, i * m)$ is a lattice point. But $a$ and $b$ are coprime by hypothesis and $i \leq b$. Thus $i * m$ is an integer if and only if $i = 0$ or $i = b$. Thus $H_L = 2$. \paragraph{(ii)}% Next we count the number of lattice points in $T$. Let $R$ be the overlapping retangle of width $w$ and height $h$, situated with bottom-left corner at $(0, 0)$. Let $I_R$ denote the number of interior lattice points of $R$. Let $I_T$ and $B_T$ denote the interior and boundary lattice points of $T$ respectively. By \nameref{C:1:07:sub:exercise-4b-eq2}, \begin{align} I_T & = \frac{1}{2}(I_R - (H_L - 2)) \nonumber \\ & = \frac{1}{2}(I_R - (2 - 2)) & \text{\nameref{par:exercise-7a-i}} \nonumber \\ & = \frac{1}{2}I_R. & \label{sub:exercise-7a-eq2} \end{align} Furthermore, since both the adjacent and opposite side of $T$ are not included in $T$ and there exist no lattice points on $T$'s hypotenuse besides the endpoints, it follows \begin{equation} \label{sub:exercise-7a-eq3} B_T = 0. \end{equation} Thus the number of lattice points of $T$ equals \begin{align} I_T + B_T & = I_T & \eqref{sub:exercise-7a-eq3} \nonumber \\ & = \frac{1}{2}I_R & \eqref{sub:exercise-7a-eq2} \nonumber \\ & = \frac{(b - 1)(a - 1)}{2}. & \text{\nameref{C:1:07:sub:exercise-4a}} \label{sub:exercise-7a-eq4} \end{align} \paragraph{Conclusion}% By \eqref{sub:exercise-7a-eq1} the number of lattice points of $S$ is equal to the sum $$\sum_{n=1}^{b-1} \floor{\frac{na}{b}}.$$ But the number of lattice points of $S$ is the same as that of $T$. By \eqref{sub:exercise-7a-eq4}, the number of lattice points in $T$ is equal to $$\frac{(b - 1)(a - 1)}{2}.$$ Thus $$\sum_{n=1}^{b-1} \floor{\frac{na}{b}} = \frac{(a - 1)(b - 1)}{2}.$$ \end{proof} \subsection*{\proceeding{Exercise 7b}}% \label{sub:exercise-7b} Derive the result analytically as follows: By changing the index of summation, note that $\sum_{n=1}^{b-1} \floor{na / b} = \sum_{n=1}^{b-1} \floor{a(b - n) / b}$. Now apply Exercises 4(a) and (b) to the bracket on the right. \begin{proof} \lean{exercise\_7b} \divider Let $n = 1, \ldots, b - 1$. By hypothesis, $a$ and $b$ are coprime. Furthermore, $n < b$ for all values of $n$. Thus $an / b$ is not an integer. By \nameref{sub:exercise-4b}, \begin{equation} \label{sub:exercise-7b-eq1} \floor{-\frac{an}{b}} = -\floor{\frac{an}{b}} - 1. \end{equation} Consider the following: \begin{align*} \sum_{n=1}^{b-1} \floor{\frac{na}{b}} & = \sum_{n=1}^{b-1} \floor{\frac{a(b - n)}{b}} \\ & = \sum_{n=1}^{b-1} \floor{\frac{ab - an}{b}} \\ & = \sum_{n=1}^{b-1} \floor{-\frac{an}{b} + a} \\ & = \sum_{n=1}^{b-1} \floor{-\frac{an}{b}} + a. & \text{\nameref{sub:exercise-4a}} \\ & = \sum_{n=1}^{b-1} -\floor{\frac{an}{b}} - 1 + a & \eqref{sub:exercise-7b-eq1} \\ & = -\sum_{n=1}^{b-1} \floor{\frac{an}{b}} - \sum_{n=1}^{b-1} 1 + \sum_{n=1}^{b-1} a \\ & = -\sum_{n=1}^{b-1} \floor{\frac{an}{b}} - (b - 1) + a(b - 1). \end{align*} Rearranging the above yields $$2\sum_{n=1}^{b-1} \floor{\frac{an}{b}} = (a - 1)(b - 1).$$ Dividing both sides of the above identity concludes the proof. \end{proof} \section*{\unverified{Exercise 8}}% \label{sec:exercise-8} Let $S$ be a set of points on the real line. The \textit{characteristic function} of $S$ is, by definition, the function $\chi_S$ such that $\chi_S(x) = 1$ for every $x$ in $S$, and $\chi_S(x) = 0$ for those $x$ not in $S$. Let $f$ be a step function which takes the constant value $c_k$ on the $k$th open subinterval $I_k$ of some partition of an interval $[a, b]$. Prove that for each $x$ in the union $I_1 \cup I_2 \cup \cdots \cup I_n$ we have $$f(x) = \sum_{k=1}^n c_k\chi_{I_k}(x).$$ This property is described by saying that every step function is a linear combination of characteristic functions of intervals. \begin{proof} TODO \end{proof} \end{document}